2021
DOI: 10.1155/2021/6117890
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mixed Traffic Flow Safety via Connected and Autonomous Vehicle Trajectory Planning with a Reinforcement Learning Approach

Abstract: The longitudinal trajectory planning of connected and autonomous vehicle (CAV) has been widely studied in the literature to reduce travel time or fuel consumptions. The safety impact of CAV trajectory planning to the mixed traffic flow with both CAV and human-driven vehicle (HDV), however, is not well understood yet. This study presents a reinforcement learning modeling approach, named Monte Carlo tree search-based autonomous vehicle safety algorithm, or MCTS-AVS, to optimize the safety of mixed traffic flow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…In recent years, RL is increasingly used in vehicle control problems in ramp metering [26,27], intersection [28,29], and freeway work zone [30], in order to improve traffic conditions. RL-based control models for AVs have a positive impact on traffic safety and efficiency [25,31,32]. For lanechanging problems of AVs, most RL-based studies focus on the lane-changing decision process [33][34][35][36][37][38], and the application of RL to lane-changing trajectory planning still needs to be supplemented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, RL is increasingly used in vehicle control problems in ramp metering [26,27], intersection [28,29], and freeway work zone [30], in order to improve traffic conditions. RL-based control models for AVs have a positive impact on traffic safety and efficiency [25,31,32]. For lanechanging problems of AVs, most RL-based studies focus on the lane-changing decision process [33][34][35][36][37][38], and the application of RL to lane-changing trajectory planning still needs to be supplemented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars focused on the interaction between autonomous driving trajectory planning and mixed traffic flow. It presented a reinforcement-learning modeling approach to optimize the safety of mixed traffic flow on a single-vehicle road controlled by a signalized intersection [6]. Government managers can develop a coordination policy based on "catch-up" to gradually increase the penetration rate of the CAV market to reduce traffic oscillation and improve road capacity [35].…”
Section: Autopilot Technologymentioning
confidence: 99%
“…Related research showed that a greater penetration rate of autonomous vehicles in traffic flow would ensure a more stable traffic flow and a lower risk [4]. Moreover, the penetration rate of autonomous driving can also optimize the average speed, delay of road traffic flow, and the safety performance of mixed traffic flow [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Koridordaki ortalama hız ve duruş sayısı ölçütlerinin beraber değerlendirilmesiyle, geleneksel yaklaşımlara göre daha hassas değerlendirme yapabilen, karma yaklaşım modelleri ortaya çıkmıştır [30]. Otonom ve bağlı araç teknolojilerinin yakın gelecekte kullanılabilme ve yaygınlaşma potansiyeli nedeniyle, son zamanlarda gerçekleştirilen çalışmalarda, bu teknolojiler dikkate alınmış ve eşgüdümlü kavşak tasarımında, otonom araçların da bulunduğu karma trafik koşullarını içeren bazı modeller geliştirilmiştir [31,32,33 Trafik mühendisliğinde, birbirleriyle ilişkili olarak yönetilen kavşaklara, eşgüdümlü kavşak; ayrı olarak yönetilen (ilişkisi bulunmayan) kavşaklara ise, ayrık (izole) kavşak adı verilmektedir. Kavşakların, eşgüdümlü şekilde çalışabilmeleri için, birbirlerine yakın mesafede (en fazla 600-800 m) ve komşu olmaları gerekmektedir.…”
Section: Gi̇ri̇ş (Introduction)unclassified